LEISHMANIOSE EM UM CANINO FÊMEA PASTOR ALEMÃO. - Baldissera, Lana Carolina Schreiber; Baldissera, Tuani Rafaela Schreiber; Inkelmann, Maria Andréia (Salão do Conhecimento, 2019)
projeto de pesquisa realizado no curso de Medicina Veterinária